Valuation of athlete endorsers – a framework for the valuation professional golfers - Palosuo, Pertti (fi=Turun yliopisto|en=University of Turku|, 2017)
Sports sponsorship is a field of marketing that has experienced steady growth since the 1980s. It has been used as a means for building brand awareness and differentiating from competitive brands. Even with steady growth, the field has experienced turmoil and debate, since the results it generates are not always calculable due to the multidimensional effects sponsorship may have. As a result, sponsorship lacks certain instruments for measuring the success of it as well as analyzing the direct value it may bring to a company. This being said, the purpose of this study is to develop a framework for the valuation of professional golfers based on quantitative big data. The research was conducted by gathering data on the athletes selected into the sample group from various different sources. Media coverage was chosen as the primary data for analysis, since based on the literature review, it was seen to be an accurate measure of sponsorship success. The sample group was chosen to consist of the top 10 golfers of the world, since there was the most sufficient data about them available. The analysis of the data was divided into two parts, the first part consisted of analyzing how the success of a player affected the amount of media generated about him. In the second part of analysis, the value of the athletes’ current sponsorship agreements was taken into account in order to arrive on how well the athletes had met their sponsors expectations on value. Finally, the mathematical equations used for analyzing were derived, in order to develop a final equation for the valuation of any athlete endorser of a certain sample group, given that the following metrics were available: tournament winnings, sponsorship income and media coverage. With these findings it was suggested that more research should be conducted in the field of athlete valuation, since the results implied certain athletes were significantly under or over appreciated compared to the sample group. It was also suggested that more research was to be conducted on the accuracy of media coverage as a metric for analyzing sponsorship success.